2017
DOI: 10.1016/j.jses.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

In vitro susceptibility of Propionibacterium acnes to simulated intrawound vancomycin concentrations

Abstract: BackgroundThere is convincing evidence supporting the prophylactic use of intrawound vancomycin powder in spinal fusion surgery and mounting evidence in the arthroplasty literature suggesting that it can reduce surgical site infections. As a result, a number of shoulder arthroplasty surgeons have adopted this practice, despite a paucity of evidence and the presence of a pathogen that is, for the most part, unique to this area of the body—Propionibacterium acnes. The purpose of this study was to evaluate the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…3,7,20,25 In addition, perioperative intravenous antibiotics, including cefazolin, ceftriaxone, vancomycin, and doxycycline, as well as vancomycin powder (intraoperatively), are administered but have varying degrees of published success. 3,[8][9][10]18,19 Lee et al have indicated the inadequacy of chlorhexidine prep alone in eradicating dermal layers of C acnes. 11 Given the persistence of C acnes despite antibiotics and skin scrub, Hsu has suggested specific attention to implant handling (avoiding dermal contact) and maximizing other methods of maintaining sterility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,7,20,25 In addition, perioperative intravenous antibiotics, including cefazolin, ceftriaxone, vancomycin, and doxycycline, as well as vancomycin powder (intraoperatively), are administered but have varying degrees of published success. 3,[8][9][10]18,19 Lee et al have indicated the inadequacy of chlorhexidine prep alone in eradicating dermal layers of C acnes. 11 Given the persistence of C acnes despite antibiotics and skin scrub, Hsu has suggested specific attention to implant handling (avoiding dermal contact) and maximizing other methods of maintaining sterility.…”
Section: Discussionmentioning
confidence: 99%
“…Standard skin prep solutions (eg, chlorhexidine gluconate, betadine soap) in addition to solutions specifically targeted to eradicate C acnes (eg, hydrogen peroxide, benzoyl peroxide, and intraoperative vancomycin powder) are commonly used; however, no consensus exists regarding a standardized protocol. 2,3,8,11,15,20,25 Despite these multifaceted approaches to prevention, periprosthetic infections with C acnes have persisted and remain a significant challenge. 21 The authors propose this study as a pilot work to identify the potential presence of culture-identifiable C acnes present on the scalpel blade used for initial skin incision despite exhaustive skin prep protocols to eradicate them.…”
mentioning
confidence: 99%
“…56 Several authors in the field consider vancomycin to be the most potent treatment against CAK. 13,25,27 The reasoning is that (1) C. acnes has consistently shown close to 100% susceptibility to vancomycin 57 and (2) vancomycin has a lower minimum bactericidal concentration against C. acnes compared with other antibiotics, [58][59][60] potentially reducing the amount of drug required to be delivered to the cornea. It is important to note, however, that just because vancomycin is considered the most potent antibiotic against CAK does not mean it is the most common for early treatment.…”
Section: Topical Interventionmentioning
confidence: 99%
“…This can help minimize the number of trays that need to be available during the procedure. and part over the deltopectoral closure [17][18][19][20][21]. A running absorbable stitch is used to close the skin along with skin glue.…”
Section: Figurementioning
confidence: 99%